A New Approximation to Classify the Liquids Measured in Microwave Frequency Range - Öztürk, Turgut (My University, 2019)
Different classification techniques have been proposed to analyze the measurement results in order to show that the liquids measured in the microwave frequency range can be separated. Furthermore, it has been shown that the proposed process can be applied successfully with different liquid quantities. Furthermore, the effect of different type containers has been demonstrated. In this context, five different liquids have been measured between 0.8-5 GHz in this study, by using ring resonator method. Thus, the ability of the proposed model has been demonstrated by the success of the measurement method and classification techniques.
Keywords: Biyoloji Çeşitliliğinin Korunması; Biyoloji; Kimya, Analitik; Kimya, Uygulamalı; Kimya, İnorganik ve Nükleer; Kimya, Tıbbi; Kimya, Organik; Fizikokimya; Ekoloji; Entomoloji; Çevre Bilimleri; Genetik ve Kalıtım; Matematik; Optik; Kuş Bilimi; Paleontoloji; Parazitoloji; Fizik, Uygulamalı; Fizik, Atomik ve Moleküler Kimya; Fizik, Katı Hal; Fizik, Akışkanlar ve Plazma; Fizik, Matematik; Fizik, Nükleer; Fizik, Partiküller ve Alanlar; Spektroskopi; İstatistik ve Olasılık; Termodinamik; Taşınım; Su Kaynakları; Bilgisayar Bilimleri, Yapay Zeka; Bilgisayar Bilimleri, Sibernitik; Bilgisayar Bilimleri, Donanım ve Mimari; Bilgisayar Bilimleri, Bilgi Sistemleri; Bilgisayar Bilimleri, Yazılım Mühendisliği; Bilgisayar Bilimleri, Teori ve Metotlar; İnşaat ve Yapı Teknolojisi; Savunma Bilimleri; Enerji ve Yakıtlar; Mühendislik, Kimya; İnşaat Mühendisliği; Mühendislik, Elektrik ve Elektronik; Çevre Mühendisliği; Mühendislik, Jeoloji; Endüstri Mühendisliği; İmalat Mühendisliği; Mühendislik, Makine; Gıda Bilimi ve Teknolojisi; Jeoloji; Yeşil, Sürdürülebilir Bilim ve Teknoloji; Görüntüleme Bilimi ve Fotoğraf Teknolojisi; Denizcilik; Metalürji Mühendisliği; Nanobilim ve Nanoteknoloji; Robotik; Telekomünikasyon